1995
DOI: 10.1111/j.1365-2125.1995.tb04494.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and gender on the pharmacokinetics of tenidap sodium in patients with rheumatoid arthritis and osteoarthritis.

Abstract: 1. This open‐label study was conducted to evaluate the effects of age and gender on the pharmacokinetics of tenidap sodium in patients with either rheumatoid arthritis (RA) or osteoarthritis (OA). 2. A total of 145 male and female patients, 80 with RA (aged 22‐91 years) and 65 with OA (aged 45‐83 years) each received a single dose of 120 mg tenidap sodium. Pharmacokinetic parameters were estimated from individual tenidap plasma concentration‐time curves determined up to 120 h post‐ dose. Tenidap plasma protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Omeprazole's effect on tenidap pharmacokinetics in dogs was determined in a previous study (21), and those results indicated that it does not alter tenidap plasma concentrations. Moreover, when tenidap was administered orally (3 mg/kg twice daily) in combination with omeprazole (20 mg/day), the therapeutic blood concentrations were similar to those observed in tenidap-treated human OA patients (24).…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Omeprazole's effect on tenidap pharmacokinetics in dogs was determined in a previous study (21), and those results indicated that it does not alter tenidap plasma concentrations. Moreover, when tenidap was administered orally (3 mg/kg twice daily) in combination with omeprazole (20 mg/day), the therapeutic blood concentrations were similar to those observed in tenidap-treated human OA patients (24).…”
Section: Methodssupporting
confidence: 52%
“…Bars show the mean and SEM histologic score (see ref. 24 for description of scoring system) for lesions from the 4-week OA dogs, the 12-week OA dogs, and the tenidap-treated dogs. P values were calculated using the MannWhitney U test.…”
Section: Macroscopic Findingsmentioning
confidence: 99%
“…In the hamster, near constant blood levels over the entire day (both feeding and non-feeding periods) are obtained when drug is administered in food (manuscript in preparation). Tenidap plasma levels averaged 6 g/ml, well below the 18-27 g/ ml achieved after giving the 120 mg dose to RA patients [16], but close to the levels of the 40 mg OA dose. Several attempts were made to reach RA therapeutic levels by dosing with tenidap in feed at higher levels.…”
Section: Tenidap Blood Levelsmentioning
confidence: 59%
“…However, the steady-state levels in the hamster exceeded the concentrations required to maintain complete suppression of cyclooxygenase. In contrast, blood levels of tenidap in the hamster are 3-5 fold below the 20 to 30 g/ml levels seen in man after a therapeutic dose of 120 mg in RA [16]. At these subclinical drug levels, the effect of tenidap on daily distance was equivalent to piroxicam and indomethacin at clinical levels.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, it appears that dosage adjustment according to age or gender is not required. [22] 3. Therapeutic Trials • Tenidap has been primarily evaluated in the treatment of patients with rheumatoid arthritis.…”
Section: Pharmacokinetic Profilementioning
confidence: 99%